(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Low back pain (LBP) is now regarded as the important cause of disability worldwide anda priority for future research on prevention and treatment. Facet joint hypertrophy is an importantpathogenesis of Low back pain. The aim of this study was to assess the effectiveness of Platelet RichPlasma and Methylprednisolone on Facet Joint Hypertrophy in Chronic Low Back Pain (LBP). Methods: This Quasi-experimental study was carried out on adult patients with chronic low back paindue to lumbar facet joint hypertrophy attended the Pain Medicine Unit, OPD and KOSAKA Pain Clinic,BSMMU, during the period of October 2019 to September 2020. The patients were randomly assignedto one of the two groups; group A (patients treated with PRP); group B (patients treated by withMethylprednisolone). After providing the allocated treatment, all patients undergone follow-upexamination 30 minutes after procedure, end of 1st week, end of 1st month and end of 3rd month forpain improvement by visual analogue scale (VAS) and for disability status by Roland Morris disabilityQuestionnaire (RMDQ)score. Follow up of the patients were carried out while they visited in Pain Clinicat mentioned intervals or over phone. The significance of the difference of the VAS and RMDQ score atthe end of 1st week, end of 1st month & end of 3rd month were tested by using unpaired t- test andchi-square test. Results: It was observed that mean ± SD of age was 42.31 ± 7.6 years for Group A and 42.29 ± 8.0 yearsfor Group B. Most of the participants in all Group A [14 (70.0%)] & in Group B [15 (75.0%)] were males.Male: Female ratio was about 2.6:1. Imaging findings shows that, Grade II degenerative changes were13(65.0%) patients of group A & 12(60.0%) patients of group B. L3/4 level involvement waspredominant, 15(75.0%) patients in Group A and 15(75.0%) in Group B. The difference was statisticallynon-significant (p>0.05) between groups. Mean VAS score at pretreatment & after 30 minutes ofintervention were not statistically significant between groups. But end of 1st week, end of 1st month andend of 3rd month follow up, VAS score decreased in both groups, but significantly reduced in Group A.In case of disability improvement, RMDQ score more decreases in group A than group B. Conclusion: Lumbar facet joint injection with platelet rich plasma (PRP) provides better pain reliefand improvement of functional status than Methylprednisolone in chronic low back pain due to lumbarfacet joint hypertrophy. JBSA 2021; 34 (2) : 3-9